Label-free, ultrahigh-speed, 3D observation of bidirectional and correlated intracellular cargo transport by coherent brightfield microscopy. Issue 19 (4th May 2017) - Huang, Yi-Fan; Zhuo, Guan-Yu; Chou, Chun-Yu; Lin, Cheng-Hao; Hsieh, Chia-Lung
Abstract : Coherent brightfield (COBRI) microscopy is a new label-free imaging and tracking technique for investigating dynamic behaviors of cell cargos traveling inside cells, such as pausing and bidirectional motions, at an ultrahigh spatiotemporal resolution. Abstract : The investigation of intracellular transport at the molecular scale requires measurements at high spatial and temporal resolutions. We demonstrate the label-free, direct imaging and tracking of native cell vesicles in live cells at an ultrahigh spatiotemporal resolution. Using coherent brightfield (COBRI) microscopy, we monitor individual cell vesicles traveling inside the cell with nanometer spatial precision in 3D at 30 000 frames per second. The stepwise directional motion of the vesicle on the cytoskeletal track is clearly resolved. We also observe the repeated switching of the transport direction of the vesicle in a continuous trajectory. Our high-resolution measurement unveils the transient pausing and subtle bidirectional motion of the vesicle, taking place over tens of nanometers in tens of milliseconds. By tracking multiple particles simultaneously, we found strong correlations between the motions of two neighboring vesicles. Our label-free ultrahigh-speed optical imaging provides the opportunity to visualize intracellular cargo transport at the nanoscale in the microsecond timescale with minimal perturbation.